A Focus Group Study Of Agrlcultural Marketing Programs - John M. Sperbeck; Marilyn Grantham; Kent Thiesse (Journal of Applied Communications, 1992)
Five focus group sessions were held involving over 50 agricultural producers and professionals who work with farmers.